Systemic desensitization through TRPA1 channels by capsazepine and mustard oil - a novel strategy against inflammation and pain - Kistner, Katrin; Siklosi, Norbert; Babes, Alexandru; Khalil, Mohammad; Selescu, Tudor; Zimmermann, Katharina; Wirtz, Stefan; Becker, Christoph; Neurath, Markus; Reeh, Peter; Engel, Matthias (Scientific Reports, 2016)
We demonstrate a novel dual strategy against inflammation and pain through body-wide desensitization of nociceptors via TRPA1. Attenuation of experimental colitis by capsazepine (CPZ) has long been attributed to its antagonistic action on TRPV1 and associated inhibition of neurogenic inflammation. In contrast, we found that CPZ exerts its anti-inflammatory effects via profound desensitization of TRPA1. Micromolar CPZ induced calcium influx in isolated dorsal root ganglion (DRG) neurons from wild-type (WT) but not TRPA1-deficient mice. CPZ-induced calcium transients in human TRPA1-expressing HEK293t cells were blocked by the selective TRPA1 antagonists HC 030031 and A967079 and involved three cysteine residues in the N-terminal domain. Intriguingly, both colonic enemas and drinking water with CPZ led to profound systemic hypoalgesia in WT and TRPV1(-/-) but not TRPA1(-/-) mice. These findings may guide the development of a novel class of disease-modifying drugs with anti-inflammatory and anti-nociceptive effects.
EVALuna2:2084

TRPA1 and substance P mediate colitis in mice - Engel, Matthias; Leffler, Andreas; Niedermirtl, Florian; Babes, Alexandru; Zimmermann, Katharina; Filipovic, Milos; Izydorczyk, Iwona; Eberhardt, Mirjam; Kichko, Tetyana; Müller-Tribbensee, Sonja; Khalil, Mohammad; Siklosi, Norbert; et al. (Gastroenterology, 2011)